2016
DOI: 10.1002/app.43456
|View full text |Cite
|
Sign up to set email alerts
|

Low k epoxy resin containing cycloaliphatic hydrocarbon with high crosslinking density

Abstract: High performance epoxy resins have attracted much research interest in the last decades. Herein, two novel epoxy monomers containing cycloaliphatic hydrocarbon, 1,4-bis(4-(N,N-diglycidylamino)phenoxy)cyclohexane (CyhEP) and 1,3-bis(4-(N,N-diglycidylamino)phenoxy)adamantane (AdaEP) were synthesized and characterized. They were cured with 4-methylhexahydrophthalic anhydride (MHHPA) to prepare the highly crosslinked thermosets. Both epoxy resins show good thermal stability (T d5 > 300 8C), high glass transition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…As can be seen from Table 1, c-FSi-BCB sheets exhibit the average D k of 2.60 with the average D f of 1.49 × 10 −3 . These results are much lower than those of the commercial low-k materials and previously reported low-k materials, such as epoxy resins (2.8-3.5), [6,24,25] polyimides (2.8-3.5), [26,27] and BCB-based resins (2.8-2.9). [28,29] Surprisingly, such good dielectric properties are still kept even after immersing c-FSi-BCB in boiling water for 96 h (see Table 1).…”
Section: Dielectric Properties and Hydrophobicity Of C-fsi-bcbcontrasting
confidence: 62%
“…As can be seen from Table 1, c-FSi-BCB sheets exhibit the average D k of 2.60 with the average D f of 1.49 × 10 −3 . These results are much lower than those of the commercial low-k materials and previously reported low-k materials, such as epoxy resins (2.8-3.5), [6,24,25] polyimides (2.8-3.5), [26,27] and BCB-based resins (2.8-2.9). [28,29] Surprisingly, such good dielectric properties are still kept even after immersing c-FSi-BCB in boiling water for 96 h (see Table 1).…”
Section: Dielectric Properties and Hydrophobicity Of C-fsi-bcbcontrasting
confidence: 62%
“…Contrastingly, there is a method to restrict the mobility of the epoxy network chains by introducing a rigid framework . Until now, we have also focused on mesogenic epoxy resins, which have higher thermal and mechanical properties than conventional epoxy resins .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Furthermore, the existence of uorinate and stiff non-polar structure can also decrease moisture absorption and improve the thermal stability of materials. 23 Sasaki 24 reported that the bisphenol A type epoxy resin cured with uorinated phthalic anhydride had the lowest dielectric constant (2.77) and dielectric loss factor (0.01) among all cured epoxy resins.…”
Section: -9mentioning
confidence: 99%